Determinants of Online Transportation Adoption: An Extended UTAUT2 Model with Loyalty Program - Lesmana, Ivan Dika; Panjaitan, Erwin Setiawan; Nurjanah, Sofiana (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study investigates the factors influencing the adoption of online transportation services, focusing on loyalty programs within the UTAUT2 framework. Online transportation platforms, such as Gojek and Grab, have revolutionized service delivery in Indonesia, yet customer retention remains a challenge. Utilizing an extended UTAUT2 model, this research incorporates constructs like Hedonic Motivation, Price Value, and Habit, alongside moderating variables such as Age, Gender, and Experience. Data from 413 active users in Medan City were analyzed using Structural Equation Modeling (SEM) via SmartPLS 3. Results highlight the critical role of loyalty programs in enhancing user engagement and retention by boosting behavioral intentions and actual usage behaviors. Findings offer actionable insights for platform providers to optimize marketing strategies and improve customer loyalty through tailored program designs.